Modalitas Politik dalam Kemenangan Saipullah Nasution dan Atika Azmi Utammi Nasution Pilkada Mandailing Natal 2024 - Reyna, Amelia Maysa; Bengkel, Bengkel; Nasution, Indra Kesuma (Mahesa Research Center, 2026)
This study aims to analyze the modalities behind the victory of Saipullah Nasution and Atika Azmi Utammi Nasution in the 2024 Mandailing Natal Regional Election. The study is based on the assumption that success in local political contests is not determined by a single form of capital, but rather by the interaction and conversion of multiple forms of capital within the political arena. Using a qualitative approach with descriptive-analytical methods, data were collected through in-depth interviews, observation, and documentation, and analyzed using Pierre Bourdieu’s theory of capital. The findings reveal that economic capital functions as a supporting prerequisite enabling political activities but does not serve as the sole determinant of victory. Social capital based on trust and community networks emerges as the most decisive factor in a highly competitive election with a narrow vote margin. Cultural capital in the form of bureaucratic and political experience shapes perceptions of leadership competence, while symbolic capital—particularly through public debate performance—acts as the ultimate source of political legitimacy. This study concludes that the 2024 Mandailing Natal election victory resulted from the contextual management